PHYSICAL STABILITY, PHOTOPROTECTIVE EFFECT, AND PRIMER IRRITATION TEST OF CREAM O/W LIME PEEL EXTRACT (CITRUS AURANTIFOLIA) AS A SUNSCREEN - WARDIYAH; SAFRINA, ULYA; CARTIKA, HARPOLIA; PUSPITA, NANDA (International Journal of Applied Pharmaceutics, 2022)
Objective: This research aimed to discover the physical stability, photoprotective effect, and primer irritation of cream oil in water (O/W) lime peel extract as sunscreen. Methods: The cream formulations were prepared using different concentrations of lime peel extract (5%, 10%, and 15%). Physical stability test performed was cycling test, storage in high temperature (40±2 °C), room temperature (25±2 °C), and low temperature (4±2 °C). Then tested for SPF value using a UV/Vis spectrophotometer and primer irritation test using rabbits. Results: All cream formulations have homogeneity, pH, viscosity, and dispersion values that meet the requirements. The SPF value of extracts and cream preparations gave Sun Protection Factor (SPF) values ​​above 15, indicating that the extracts and the three formulas had sunscreen protection activity in the ultra-category. The SPF value and total phenol decreased in cold and hot storage but were relatively stable at room temperature storage. The results of the irritation test on rabbits showed moderate irritation in the base group and slight irritation in the extract group. Conclusion: Lime peel extract sunscreen cream has good physical stability, a photoprotective effect in the ultra-category, and mild to moderate level of irritation.